Linear dichroism infrared resonance in overdoped, underdoped, and optimally doped cuprate superconductors - Mukherjee, A.; Seo, J.; Arik, M. M.; Zhang, H.; Zhang, C. C.; Kirzhner, T.; George, D. K.; Markelz, A. G.; Armitage, N. P.; Koren, G.; Wei, J. Y. T.; Cerne, J. (Physical Review B, 2020)
By measuring the polarization changes in terahertz, infrared, and visible radiation over an extended energy range (3-2330 meV), we observe symmetry breaking in cuprate high-temperature superconductors over wide energy, doping, and temperature ranges. We measure the polarization rotation (Re[theta(F)]) and ellipticity (Im[theta(F)]) of transmitted radiation through thin films as the sample is rotated. We observe a twofold rotational symmetry in theta(F), which is associated with linear dichroism (LD) and occurs when electromagnetic radiation polarized along one direction is absorbed more strongly than radiation polarized in the perpendicular direction. Such polarization anisotropies can be generally associated with symmetry breakings. We measure the amplitude of the LD signal and study its temperature, energy, and doping dependence. The LD signal shows a resonant behavior with a peak in the few hundred meV range, which is coincident with the midinfrared optical feature that has been associated with the formation of the pseudogap state. The strongest LD signal is found in underdoped films, although it is also observed in optimally and overdoped samples. The LD signal is consistent with an electronic nematic order which is decoupled from the crystallographic axes as well as novel magnetoelectric effects.
Keywords: Materials Science; Physics

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
Keywords: bi2te3; Physics

Ultrafast Carriers Dynamics in GaSb/Mn Random Alloys - Ye, S.; Knab, J.; Chen, J.-Y.; Wang, S.; Cheon, M.; Luo, H.; Markelz, A. G. (Proceedings of the 28th International Conference on the Physics of Semiconductors, 2006)

Direct measurements of optical phonons in SrTiO3 nanosystems - Wolpert, D; Korolev, K; Sachs, S; Knab, J; Cox, W; Cerne, J; Markelz, A.G; Zhao, T; Ramesh, R; Moeckly, B.H (Physica E: Low-dimensional Systems and Nanostructures, 2003)
We use terahertz time domain spectroscopy to examine finite size effects on the optical phonon modes in SrTiO3 thin films. In temperature-dependent measurements we find a near absence of mode softening in the TO1 phonon frequency. Furthermore we see an increase in the soft mode frequency with reduced thickness. Both of these results correlate well with the reduced dielectric response observed for nanoscale ferroelectric systems.
Keywords: Ferroelectrics; Finite size; Mode softening; phonons; Strontium titanate; Terahertz

Finite size effects in ferroelectric nanosystems: Absence of mode softening - D. Wolpert; W. Cox; J. Cerne; A. Markelz; T. Zhao; R. Ramesh (2003 Nanotechnology Conference and Trade Show - Nanotech, 2003)
We present measurements of the mode softening behavior for PbZr 0.5Ti0.5O3 (PZT(50)) thin films using terahertz time domain spectroscopy (TTDS). The films were grown using pulsed laser deposition (PLD) techniques on silicon substrates to study how reduced size affects the mode softening behavior. At room temperature two modes are observed at 1.1 THz (37 cm-1) and at 2.3 THz (77 cm-1). As the temperature is increased toward Tc we do not see strong mode softening, but rather a spectral weight transfer from the high frequency mode to the low frequency mode. This absence of mode softening is more dramatic than that reported by other investigators[1]. We will discuss the possible sources for this discrepancy. These results suggest a change in lattice dynamics for nanoscale ferroelectric films that may be highly dependent on the sample preparation technique.
Keywords: Ferroelectric materials; Fourier Transform Infrared Spectroscopy; Frequency ranges; Lead compounds; Mode softening; nanostructured materials; Natural frequencies; Optical modes; Permittivity; phase transitions; phonons; Routers; Thermal effects

Protein flexibility and conformational state: A comparison of collective vibrational modes of wild-type and D96N bacteriorhodopsin - Whitmire, S. E.; Wolpert, D.; Markelz, A. G.; Hillebrecht, J. R.; Galan, J.; Birge, R. R. (Biophysical Journal, 2003)
Far infrared ( FIR) spectral measurements of wild-type (WT) and D96N mutant bacteriorhodopsin thin films have been carried out using terahertz time domain spectroscopy as a function of hydration, temperature, and conformational state. The results are compared to calculated spectra generated via normal mode analyses using CHARMM. We find that the FIR absorbance is slowly increasing with frequency and without strong narrow features over the range of 2-60 cm(-1) and up to a resolution of 0.17 cm(-1). The broad absorption shifts in frequency with decreasing temperature as expected with a strongly anharmonic potential and in agreement with neutron inelastic scattering results. Decreasing hydration shifts the absorption to higher frequencies, possibly resulting from decreased coupling mediated by the interior water molecules. Ground-state FIR absorbances have nearly identical frequency dependence, with the mutant having less optical density than the WT. In the M state, the FIR absorbance of the WT increases whereas there is no change for D96N. These results represent the first measurement of FIR absorbance change as a function of conformational state.
Keywords: angstrom resolution; Biophysics; dna; films; frequency; harmonic-analysis; inelastic neutron-scattering; large systems; mixed basis; normal-modes; purple membranes; structural-changes; transform infrared-spectroscopy

Terahertz Applications to Biomolecular Sensing - Markelz, A. G.; Whitmire, S. E. (International Journal of High Speed Electronics and Systems, 2003)

Terahertz applications to biomolecular sensing - Markelz, Andrea G; Whitmire, Scott E (International Journal of High Speed Electronics and Systems, 2003)

Ultrafast THz spectroscopy of photoactive biomolecules - Chen, J.-Y.; Whitmire, S. E.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Ultrafast Phenomena in Semiconductors VII, 2003)

THz time domain spectroscopy of biomolecular conformational modes - Markelz, Andrea; Whitmire, Scott; Hillebrecht, Jay; Birge, Robert (Physics in Medicine & Biology, 2002)

Terahertz Time domain spectroscopy of the M intermediate state of Bacteriorhodopsin - Whitmire, S.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Proceedings of the 26th International Conference on Infrared and Millimeter Waves, 2001)

Third Harmonic Generation in a Gaas/Algaas Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A. G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Hot Carriers in Semiconductors, 1996)

Undressing a collective intersubband excitation in a quantum well - Craig, K.; Galdrikian, B.; Heyman, J. N.; Markelz, A. G.; Williams, J. B.; Sherwin, M. S.; Campman, K.; Hopkins, P. F.; Gossard, A. C. (Physical Review Letters, 1996)
We have experimentally measured the 1-2 intersubband absorption in a single 40 nm wide modulation-doped Al0.3Ga0.7As/GaAs square quantum well as a function of frequency, intensity, and charge density. The low-intensity depolarization-shifted absorption occurs near 80 cm(-1) (10 meV or 2.4 THz), nearly 30% higher than the intersubband spacing. At higher intensities, the absorption peak shifts to lower frequencies. Our data are in good agreement with a theory proposed by Zaluzny, which attributes the redshift to a reduction in the depolarization shift as the excited subband becomes populated.

Third harmonic generation in a GaAs/AlGaAs Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A.G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Proceedings of the International Conference on Hot Carriers in Seminconductors, 1995)

Site-selective oxygen-isotope substitution in YBa2Cu3O7−δ - Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Huitgren, C. T.; Nickel, J. H.; Hamilton, J. C.; McCarty, K. F. (Physical Review B, 1991)
We report selective substitution of oxygen-18 and oxygen-16 isotopes into the inequivalent oxygen lattice sites in YBa2Cu3O7−δ. The technique involves gas-phase diffusion and exploits the site dependence of diffusion rates. The CuO2-plane [O(2),O(3)] sites of YBa2Cu3O7−δ can be filled with 18O while the apical [O(4)] and CuO-chain sites [O(1)] contain 16O (the opposite distribution can also be made). The site-selective isotope occupation has been confirmed by Raman spectroscopy. Our method will permit experiments to determine the contributions of the different oxygen sites to the isotope effect, in order to locate the pairing interaction within the unit cell.

8 NEW HIGH-TEMPERATURE SUPERCONDUCTORS WITH THE 1-2-4 STRUCTURE - Morris, D. E.; Nickel, J. H.; Wei, J. Y. T.; Asmar, N. G.; Scott, J. S.; Scheven, U. M.; Hultgren, C. T.; Markelz, A. G.; Post, J. E.; Heaney, P. J.; Veblen, D. R.; Hazen, R. M. (Physical Review B, 1989)

OXYGEN CONCENTRATION EFFECT ON TC OF THE BI-CA-SR-CU-O SUPERCONDUCTOR - Morris, D. E.; Hultgren, C. T.; Markelz, A. M.; Wei, J. Y. T.; Asmar, N. G.; Nickel, J. H. (Physical Review B, 1989)

SMALL OXYGEN ISOTOPE SHIFT IN YBA2CU3O7 - Morris, D. E.; Kuroda, R. M.; Markelz, A. G.; Nickel, J. H.; Wei, J. Y. T. (Physical Review B, 1988)

SPECIFIC-HEAT MEASUREMENTS ON SUPERCONDUCTING BI-CA-SR-CU AND TL-CA-BA-CU OXIDES - ABSENCE OF A LINEAR TERM IN THE SPECIFIC-HEAT OF BI-CA-SR-CU OXIDES - Fisher, R. A.; Kim, S.; Lacy, S. E.; Phillips, N. E.; Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Ginley, D. S. (Physical Review B, 1988)